TINGKAT PENGETAHUAN MASYARAKAT SEKITAR OBSERVATORIUM BOSSCHA LEMBANG MENGENAI POLUSI CAHAYA - Laila Nurfarida; Pawit Muhammad Yusup; Neneng Komariah (Jurnal Kajian Informasi dan Perpustakaan, 2017)
The purpose of this research is to determine the knowledge level of the society around Bosscha Observatory in Lembang about light pollution. The research was conducted using a survey method to  98 respondents in Lembang Village, Lembang District, West Bandung District. Based on the results of the research, it is revealed that the knowledge level  of the Society  around  Bosscha Observatory Lembang about light pollution is categorized as high. It is based on the research on four dimensions of knowledge with high results for factual, conceptual, and procedural knowledge, thus  indicating that the public knows well the term, indicators, causes, disorder, harmful nature, the countermeasure solution , the countermeasure techniques, and the criteria of when to apply the  procedure of light pollution countermeasure. Then, the next is medium results for metacognition knowledge indicating that the public knows enough information resources, the importance of countermeasures, and the awareness of the knowledge about light pollution. Therefore  the society is expected to be wiser in using artificial light and contribute to reducing light pollution. Keywords: Knowledge, Light Pollution, Bosscha Observatory